2013
DOI: 10.1128/jvi.01578-12
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus Viroplasm Proteins Interact with the Cellular SUMOylation System: Implications for Viroplasm-Like Structure Formation

Abstract: e Posttranslational modification by SUMO provides functional flexibility to target proteins. Viruses interact extensively with the cellular SUMO modification system in order to improve their replication, and there are numerous examples of viral proteins that are SUMOylated. However, thus far the relevance of SUMOylation for rotavirus replication remains unexplored. In this study, we report that SUMOylation positively regulates rotavirus replication and viral protein production. We show that SUMO can be covalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 38 publications
3
26
0
Order By: Relevance
“…Immunofluorescence staining was performed as previously described19. Analysis of the samples was carried out on an Axio Vert.A1 microscope (Zeiss) with ZEN software.…”
Section: Methodsmentioning
confidence: 99%
“…Immunofluorescence staining was performed as previously described19. Analysis of the samples was carried out on an Axio Vert.A1 microscope (Zeiss) with ZEN software.…”
Section: Methodsmentioning
confidence: 99%
“…We then examined the effect of SUMOylation of NS5A on protein–protein interaction. Because NS5A interacted with NS5B and formed the HCV replication complex , we investigated the effect of SUMOylation on protein interaction between NS5A and NS5B. We confirmed that NS5B strongly interacted with wild‐type NS5A.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro SUMO conjugation assays were performed on [ 35 S]methionine-labeled in vitro -transcribed/translated proteins as described previously25. Briefly, [ 35 S]methionine-labelled proteins were incubated with E1 in a 10 μL reaction including an ATP regenerating system (50 mM Tris pH 7.6, 5 mM MgCl 2 , 2 mM ATP, 10 mM creatine phosphate, 3.5 U/mL of creatine kinase and 0.6 U/mL of inorganic pyrophosphatase), 10 μg SUMO1 or SUMO2, and 600 ng Ubc9.…”
Section: Methodsmentioning
confidence: 99%